ChemInform Abstract: Catalytic Rearrangement of 2‐Alkoxy Diallyl Alcohols: Access to Polysubstituted Cyclopentenones. Issue 31 (14th July 2016) - Lempenauer, Luisa; Dunach, Elisabet; Lemiere, Gilles
Abstract: Only 1 mol% of catalyst is required for a successful preparation of the desired title compounds.